2013
DOI: 10.1186/2036-7902-5-s1-s5
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid diverticulitis: US findings

Abstract: Acute diverticulitis (AD) results from inflammation of a colonic diverticulum. It is the most common cause of acute left lower-quadrant pain in adults and represents a common reason for acute hospitalization, as it affects over half of the population over 65 years with a prevalence that increases with age. Although 85% of colonic diverticulitis will recover with a nonoperative treatment, some patients may have complications such as abscesses, fistulas, obstruction, and /or perforation at presentation. For thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…In anticipating potentially life-threatening complications of acute diverticulitis (eg, peritonitis, perforation, intra-abdominal abscesses, fistulas, and obstructions), CT has become the diagnostic modality of choice in most of the western world. 3,7,14,19,20 In cases in which abscesses are detected, CT can further guide percutaneous drainage and provide an indication for embolization of diverticular bleeding. However, CT is not readily available in emerging and underdeveloped nations, 21 requires increased time for interpretation by a radiologist, exposes the patient to ionizing radiation, and, unlike sonography, is not cost-effective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In anticipating potentially life-threatening complications of acute diverticulitis (eg, peritonitis, perforation, intra-abdominal abscesses, fistulas, and obstructions), CT has become the diagnostic modality of choice in most of the western world. 3,7,14,19,20 In cases in which abscesses are detected, CT can further guide percutaneous drainage and provide an indication for embolization of diverticular bleeding. However, CT is not readily available in emerging and underdeveloped nations, 21 requires increased time for interpretation by a radiologist, exposes the patient to ionizing radiation, and, unlike sonography, is not cost-effective.…”
Section: Discussionmentioning
confidence: 99%
“…In the largest meta-analysis of its type, approximately 630 patients (across 6 studies) were evaluated with sonography, and 684 patients (across 8 studies) were evaluated with CT; both yielded similar accuracy, with 92% and 94% summary sensitivity and 90% and 99% summary specificity, respectively. [5][6][7][8] Additionally, Laméris et al 9 identified several clinical and laboratory parameters aimed toward accurately diagnosing mild diverticulitis, which when positive obviated the need to perform CT, including localized left lower quadrant tenderness, absence of vomiting, and elevated Creactive protein levels. 10 However, when uncomplicated acute diverticulitis was clinically suspected but not all 3 of these criteria were met, the results were more variable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This condition is mostly caused by adhesions (60-70%) and volvulus (25%) [12], but other conditions can predispose, i.e., intussusception (<5%), colorectal carcinoma (3.7%), hernia (1.4%), appendicitis (0.5%), and diverticulitis (0.3%) [31][32][33]. Adhesions are more frequently seen in later stages of pregnancy with increasing rates from the first to the third trimester (6 vs. 45%) [31,32].…”
Section: Intestinal Diseasesmentioning
confidence: 99%
“…Both low and high frequency ultrasound examination is appropriate for the identification of diverticula. The diverticula appear in the US image as reduced gut signature due to the absence/thinning of muscularis propria, or as bright “ears” out of the intestinal wall with acoustic shadow caused by the presence of intradiverticular gas[48]. In case of diverticulitis, intestinal wall thickening, pericolic inflammation and fluid could be detected beside the diverticula.…”
Section: Diverticular Disease and Diverticulitismentioning
confidence: 99%